A Novel Multiplayer Screen-Based Simulation Experience for African Learners Improved Confidence in Management of Postpartum Hemorrhage - Taekman, Jeffrey M.; Foureman, Megan F.; Bulamba, Fred; Steele, Michael; Comstock, Emily; Kintu, Andrew; Mauritz, Amy; Olufolabi, Adeyemi (Frontiers in Public Health, 2017)
Intro: Despite improvements in the rate of maternal mortality worldwide, more than 250,000 women die each year during the perinatal period, many from postpartum hemorrhage. Postpartum hemorrhage remains a global challenge, affecting thirteen million women each year, and is a leading cause of maternal mortality in Asia and Africa. In the United States of America (USA), care of critically ill patients is often practiced using mannequin-based simulation. Mannequin-based simulation offers many challenges in global health education and training, particularly in Low or Middle Income Countries. We have developed a novel multiplayer screen-based simulation that enables the practice of patient care and team coordination of postpartum hemorrhage in a virtual world. We used this simulation as the centerpiece of a simulation experience for learners in Mulago, Uganda. We hypothesized that a multi-player screen-based simulation experience would increase learner confidence in their ability to manage postpartum hemorrhage. Methods: The study design was a simple pre and post intervention survey. Forty-eight interprofessional subjects participated in one of nine 1-hour simulation sessions using the postpartum hemorrhage software. A fifteen-question self-assessment administered before and after the intervention was designed to probe the areas of learning as defined by Bloom and Krathwohl: affective, cognitive, and psychomotor. Results: Combined confidence scores increased significantly overall following the simulation experience and individually in each of the three categories of Bloom’s Taxonomy: affective, cognitive, and psychomotor. Conclusion: We provide preliminary evidence that multiplayer screen-based simulation represents a scalable, distributable form of learning that may be used effectively in global health education and training. In addition, despite our intervention being screen-based, our subjects showed improved confidence in their ability to perform psychomotor tasks. Although there is precedent for mental rehearsal improving performance, further research is needed to understand this finding.